PARAMETRIC STUDY OF FUNCTIONALLY GRADED MATERIALS USING THE HAAR WAVELET METHOD - Писаренко, Олександр (SWorldJournal, 2024)
This paper studies the effect of frequency-dependent damping of composite materials on the kinematic characteristics of rotating laminated composite cylindrical shells. Based on the Haar wavelet method, the dynamic equations and corresponding boundary con